Recent progress on anti-cancer of amide appended heterocyclic and its possible therapeutic applications. A review drug progress for cancer therapeutics. (Funded work) - YASSER HUSSEIN EISSA MOHAMMED,; SHAUKATH ARA KHANUM, (International Journal of Pharma and Bio Sciences, 2018)
Cancer is caused by malignant neoplasm related to unregulated cell growth. Neoplastic cells often reside in distinctive tumor hypoxia armed with a series of adaptive responses including oxidative stress, defective apoptotic machinery and neoangiogenesis, through that further confer cell survival improvement. There is a major unmet medical need for effective and well tolerated treatment options for cancer. The search now seeks to identify active biomolecules with multiple targets.This study has shown ambivalent results causing a prolonged over the value of drug and paving the way for the medicinal chemistry investigations of thiazole, pyridazine and pyrone analogues. Thiazole, pyridazine and pyrones nuclei show a broad spectrum of pharmaceutical applications. Thus, in this article, we have taken a step to review the evidences for cancer treatment, as well as to discuss the possible factors limiting the effectiveness of anti-cancer agents and to offer a recommendation for the future research of budding scientists on these therapies for the treatment of cancer has been taken.